MATH SOLVE

4 months ago

Q:
# How do I do this please help me I will give you thank even tho it’s not important Ahahah please help me

Accepted Solution

A:

Answer:(-2 , 5)(-1 , 0)(1 , -4)(3 , 0)(4 , -5)Step-by-step explanation:First solve the equation:x² - 2x - 3Find two numbers with have a sum of -2 and a product of -3.-3 and 1(x - 3)(x + 1)Solve for x:x - 3 = 0x = 3x + 1 = 0x = -1You know that the graph will cross the x-axis at -1 and 3.(-1 , 0)(3 , 0)You know that the graph is positive.Complete the square to find the vertexx² - 2x - 3(x - 1)² = x² - 2 + 1x² - 2x - 3 = x² - 2 + 1 - 2 = (x - 1)² - 2 1 = 0x = 1Substitute into the original equation:x² - 2x - 3 =1² - (2 * 1) - 3 =1 - 2 - 3 =-4(1 , -4)You can input any two numbers within -10 and 10. Such as -2 and 4.x² - 2x - 3 =-2² - (2 * -2) - 3 =4- -4- 3 =5(-2 , 5)x² - 2x - 3 =4² - (2 * 4) - 3 =16 - 8 - 3 =-5(4 , -5)